Effects of the Covid-19 pandemic on international trade in the SADC region - Davidzo H. Mapuvire; Victor K. Mapuvire (MSU Press, 2023)
International trade within the Southern Africa Development Community (SADC) region has witnessed a significant level of growth within the past few years. This phenomenon has been mirroring what has been occurring within the African continent at large, and it indeed shows great economic growth prospects for the continent. However, the coming of the Covid-19 pandemic disrupted international trade and created a lot of uncertainty. Therefore, this paper focused on the global trade inter-connectedness in the SADC region before and after the Covid-19 outbreak. The main objective of this research was to find out how the Covid-19 global pandemic has affected international trade within SADC. This study was qualitative in nature and the research employed secondary data collection methods. Secondary methods involved documentary review where journal articles, academic books, newspapers and research articles were examined to gain insights into the issues relating to the effects of global pandemics (Covid-19) on trade in SADC. The research revealed that the global economy, including the economy of SADC countries was facing some challenges even before the Covid-19 outbreak. It was noted that as a result of the pandemic, the governments within SADC introduced a raft of measures in attempts to address the challenges emanating from the disruptions brought about by the Covid-19 pandemic. Further, the pandemic posed a serious threat to international trade for SADC as a region and thus eroded any gains made towards trade liberalization over the past few decades with its impact on trade being more severe than those of the 2008-09 Global Financial Crisis.